A prediction of the long-term future of tin - A. G. W. Knock (The Southern African Institute of Mining and Metallurgy, 1979)
Logistic curves are used in the prediction of the primary production of tin metal from estimated worldwide resources. Such curves are asymptotic to the total cumulative reserves, which are a function of prevailing metal prices and total resources. The figures for tin resources are based on the findings of Robertson and of Brobst and Pratt, the latter authors including estimates of undiscovered deposits. It is suggested that tin production will slump from the present level to 100000 long tons per annum by the end of the century, but will reach a new peak of 200 000 long tons some thirty years later. It appears that production will never exceed 300000 long tons per annum unless substantial new resources, excluding those predicted, are discovered.